Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
DOI: 10.22215/etd/2013-10387
|View full text |Cite
|
Sign up to set email alerts
|

Endwall Flows in Transonic Turbine Cascades

Abstract: The results of an investigation of the midspan and endwall flows in transonic linear turbine cascades are documented here. A family of five turbine cascades with different levels of flow turning and aerodynamic loading were used for this study to quantify the effects of these parameters on loss generation in compressible flows. Experimental data on these flows are scarce in the open literature. In addition, the application of two different passive flow control techniques for reducing the endwall losses is exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 70 publications
(160 reference statements)
0
5
0
Order By: Relevance
“…The simulation methodology was previously validated using data collected at the Pratt and Whitney Canada (PWC) high-speed wind tunnel (HSWT) at Carleton University in Ottawa, Canada by Sooriyakumaran. 11 For a detailed description of the validation process or the wind-tunnel apparatus, the reader is referred to the work of Owen 12 and Taremi, 13 respectively.…”
Section: Simulation Setupmentioning
confidence: 99%
“…The simulation methodology was previously validated using data collected at the Pratt and Whitney Canada (PWC) high-speed wind tunnel (HSWT) at Carleton University in Ottawa, Canada by Sooriyakumaran. 11 For a detailed description of the validation process or the wind-tunnel apparatus, the reader is referred to the work of Owen 12 and Taremi, 13 respectively.…”
Section: Simulation Setupmentioning
confidence: 99%
“…Figure 19 presents the contour plots of the streamwise vorticity coefficient K ω,s for the cases of Re out,is = 70 k and M out,is = 0.7, 0.9, and 0.95 measured with the PIV and the 5HP. The streamwise vorticity coefficient was computed according to the method of Gregory-Smith et al [41] and employing the normalization reported by Taremi [42]…”
Section: Resultsmentioning
confidence: 99%
“…( 10)) as suggested in Ref. [42]. The total pressure gradient at the outlet measurement plane, ∂(lnP 0,out )/∂z, was taken from the 5HP measurements…”
Section: Resultsmentioning
confidence: 99%
“…For a detailed description of the experimental facility, an interested reader is referred to either the work of Sooriyakumaran 8 or Taremi. 12 A few key differences between the experiment and CFD are listed next. First, the dimensions of the airfoils as well as the working fluid properties have been scaled from engine conditions to appropriate environments for the experimental facility.…”
Section: Boundary and Initial Conditionsmentioning
confidence: 99%